Typical Language Anomalies in Written Professional Communication - Shulska, Nataliia; Kostusiak, Nataliia; Hromyk, Larysa; Nasminchuk, Iryna; Ostapchuk, Svitlana; Mezhov, Oleksandr; Zavarynska, Iryna; Dubrovskyi, Roman; Kominiarska, Iryna; Poliak, Iryna (My University, 2024)
The article analyzes typical language anomalies in the written professional communication of employees of public authorities of Ukraine. The role of linguistic competence in the professional profile of a modern public servant is determined. On the basis of negative material extracted from the texts of official documents, typical error-prone areas at the level of spelling, vocabulary, grammar (morphology and word formation) are identified and characterized. The author suggests relevant literary correspondences to the analyzed anomalies. The material of the study is constructions of modern official business style containing erroneous punctuation. The anomalies were extracted from the texts of official documents posted in the public domain on the websites of Ukrainian government agencies. It has been established that the most common errors at the level of spelling are disregard for the norms of the new edition of Ukrainian spelling, violation of the rules of euphony, and incorrect use of capital letters in the names of institutions, documents, and holidays. Spelling mistakes in documents are caused by non-compliance with the rules of technical typing, including unjustified use of hyphens instead of dashes, errors of incremental numerals, word abbreviations, use of dates, neglect of indents, and identical quotation marks. The lexical anomalies identified in the use of unmotivated tautology, pleonasm, words in an unusual meaning or violation of their compatibility are recorded. Among the most common morphological errors in the official business style, there are inaccuracies in the use of the vocative case when addressing the addressee in business correspondence, surname declension, use of the dative case, agreement of numerals with nouns, declension of numeral forms, and use of passive verb constructions with - ся. Syntactic anomalies include erroneous ‘copied’ phrases in which prepositions that are not typical for a particular context are used to express semantic and syntactic relations.
Keywords: language culture; error; professional communication; official business sphere; public servants